USE OF DIFFERENT HAEMORRHOIDECTOMY METHODS AND A GENERAL ASSESSMENT OF POST-OPERATIVE VALUES - Dr. IBRAHIM MUSTAFA SIDDIK,Dr. Fadhil Hussein Faris Ali,Dr. EMAD KHALID MOHAMMED, (Zien Journals, 2022)
Hemorrhoids is one of the most common health problems faced by internists, as the definition and aetiology arediscussed, and hemorrhoids is often a difficult condition in our daily practice.GoalThis research aims to use different methods of hemorrhoidectomy and general evaluation of postoperative values ofIraqi patients.Materials and methodIn this study, 90 hemorrhoidal patients who agreed to participate in the study were recruited.An observational, descriptive, and retrospective study was conducted on patients with hemorrhoids using datacollected from several different hospitals in Iraq from July 2021 to November 2021.A questionnaire was designed by expert physicians for patients with hemorrhoids group from the Ministry of PublicHealth, a database was created using Microsoft Access, statistical analysis was performed using IBM SOFT SPSS 22for Windows, and the final document was prepared with Microsoft Office package.ConsequencesThe result found in this study is 90 patients were collected and divided into two groups (open 40 and closed 50)between the ages of 20 to 60 years.In this study, the ASA score was relied upon for the purpose of measuring the type of process pattern. In addition,it was relied on to classify the degrees of pain and complications that cause by Iraqi patients. Weak results werefound in the open group, more than 0 in the closed group, where a statistically significant relationship of 0.041 wasfound.ConclusionWe conclude from this study that closed-type operations are better than open-type in stopping bleeding and closingthe wound in the anus in the future of the patient.
Keywords: Haemorrhoidectomy, Opened, Closed, Post-operative values